The diary of mattie spenser eaudiobook - Dallas, Sandra (Recorded Books, 2012)
No one is more surprised than Mattie Spenser herself when Luke Spenser, considered the great catch of their small Iowa town, asks her to marry him. Less than a month later, they are off in a covered wagon to build a home on the Colorado frontier. Mattie's only company is a slightly mysterious husband and her private journal, where she records the joys and frustrations not just of frontier life, but also of a new marriage to a handsome but distant stranger. As she and Luke make life together on the harsh and beautiful plains, Mattie learns some bitter truths about her husband and the girl he left behind and finds love where she least expects it. Dramatic and suspenseful, this is an unforgettable story of hardship, friendship and survival. "One of the bright new voices in historical fiction ... Dallas's authentic period details, her colorful minor characters, and most of all Mattie herself lend charm and emotional truth to this appealing marital and pioneering adventure."—Publishers Weekly